Fairness Perception, Trust Perception, and Relationship Quality in Agricultural Supply Chains. (10th March 2021) - Sun, Yuling; Zhu, Zeyu; Yang, Hui
Abstract : Suppliers are important members of the agricultural supply chain. Moreover, their behavior decisions may affect the sustainable development of the agricultural supply chain. Considering agricultural supplier trust, this study examines the direct impact of trust perception on relationship quality and the indirect impact of supplier fairness perception on relationship quality. Based on the survey data of agricultural product suppliers, this study uses the structural equation model method for empirical analysis. The analysis results show that both fairness perception and trust perception have a significant positive impact on the relationship quality of the agricultural supply chain. Trust perception particularly has a positive direct impact on the relationship quality of the agricultural supply chain, while fairness perception has an indirect influence on the relationship quality of the agricultural supply chain through trust perception. In addition, information sharing, price satisfaction, income level, and environmental certainty have a significant positive impact on suppliers' fairness perception. Therefore, retailers comprehensively consider both fairness perception and trust perception of suppliers, which will help improve the relationship quality of the supply chain.